The comparison of manual and mechanical anastomosis after total pharyngolaryngoesophagectomy - Wang, Kexi; He, Xiaotian; Wu, Duoguang; Wang, Kefeng; Li, Yuquan; Wang, Wenjian; Hu, Xueting; Lei, Kai; Tan, Binghua; Liang, Ruihao; Cai, Qian; Wang, Minghui (Frontiers in Oncology, 2023)
Background: Total pharyngolaryngoesophagectomy (TPLE) is considered as a curative treatment for hypopharynx cancer and cervical esophageal carcinomas (HPCECs). Traditional pharyngo-gastric anastomosis is usually performed manually, and postoperative complications are common. The aim of this study was to introduce a new technique for mechanical anastomosis and to evaluate perioperative outcomes and prognosis. Methods: From May 1995 to Nov 2021, a series of 75 consecutive patients who received TPLE for a pathological diagnosis of HPCECs at Sun Yat-sen Memorial Hospital were evaluated. Mechanical anastomosis was performed in 28 cases and manual anastomosis was performed in 47 cases. The data from these patients were retrospectively analyzed. Results: The mean age was 57.6 years, and 20 % of the patients were female. The rate of anastomotic fistula and wound infection in the mechanical group were significantly lower than that in the manual group. The operation time, intraoperative blood loss and postoperative hospital stays were significantly higher in the manual group than that in the mechanical group. The R0 resection rate and the tumor characteristics were not significantly different between groups. There was no significant difference in overall survival and disease-free survival between the two groups. Conclusion: The mechanical anastomosis technology adopted by this study was shown to be a safer and more effective procedure with similar survival comparable to that of manual anastomosis for the HPCECs patients.